Exercise as a drug for glucose management and prevention in type 2 diabetes mellitus. (August 2021) - Sgrò, Paolo; Emerenziani, Gian Pietro; Antinozzi, Cristina; Sacchetti, Massimo; Di Luigi, Luigi
Abstract: Physical inactivity and sedentary behavior are risk factors for type 2 diabetes mellitus (T2DM). Therefore, physical exercise (PE) together with medical treatment might be considered as a key strategy to counteract T2DM. Glycemic control is a central objective in the prevention and management of T2DM, and PE might be able to substantially affect the processes that determine it. Just like a drug, exercise can be dosed based on the characteristics of the individual to increase its benefits and reduce side effects. In this brief review, the mechanisms underlying the effects of PE on glucose metabolism in muscle are illustrated, and the effects of modulation of the parameters characterizing this atypical "drug" on glucose homeostasis are described.